BEHAVIORAL OBSERVATION OF “OVERDUE LEADER” - MIRZOYAN, VALERI (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
In the article, the author introduces the concept of “overdue leader” not only temporarily, but also from the point of view of the leader’s ability to realize the fact of ending his own mission. The timely departure of the leader is one of the main conditions for ensuring democratic principles of governance, while the unreasonable “delay” of the leader creates a lot of personal and social problems. The appearance of an “overdue leader” indicates a serious illness of the entire social organism, in particular, the absence of mutual balances between the branches of govern-ment, the imperfection of the political system, the fragmentation of the opposition, and the incapacity of civil society institutions. The behavioral degradation of the leader himself is inevitable – the strengthening of power, lust, populism, cynicism, narcissism, Machiavellianism, intolerance, aggressiveness, etc.
Keywords: leadership, “overdue leader”, democratic principles of governance, behavioral degradation of a leader, power-loving